Principles of conservation biology - Meffe, Gary K. (Sinauer, 1997)
Principles of Conservation Biology, Second Edition, is a major revision of the most comprehensive textbook on conservation biology. First published in 1994, and richly praised by reviewers, teachers, and students, Principles was adopted for courses at more than 145 colleges and universities in the United States and Canada. Written by leading experts in the field, it is intended for use in conservation biology courses at the advanced undergraduate (junior and senior) and graduate levels, as well as by researchers and practitioners, and assumes a basic background in biology and ecology.